Support gaps during the COVID-19 pandemic: Sex differences and effects on well-being. (October 2021) - Holmstrom, Amanda J.; Shebib, Samantha J.; Boumis, Josephine K.; Allard, Amanda; Mason, Adam J.; Lim, Jong In
During times of stress, supportive communication can buffer individuals from experiencing negative outcomes. However, the COVID-19 pandemic has substantially altered the interactions people rely on for support, which may influence the supportive messages they desire and receive. When people receive quantities of support that differ from what they desire, they experience support gaps, which are often associated with negative outcomes. The present study examines: (a) support gaps in close relationships under shelter-in-place orders issued in response to the pandemic; (b) how support gaps may be moderated by recipient and provider sex; and (c) relationships between support gaps and loneliness, stress, and relational satisfaction. Data were collected in Spring 2020 from community members across the United States and students at a large Midwestern university ( N = 273). Participants reported on five types of support desired and received from their closest relational partner. Unexpectedly, participants generally reported receiving more support than desired, though this finding was qualified by their biological sex and the biological sex of their partner. As expected, support deficits were primarily associated with negative outcomes. Surplus esteem support was positively associated with relational satisfaction and negatively associated with perceived stress. Results are discussed in terms of theoretical implications for support gaps research and theory as well as pragmatic implications for individuals experiencing a global, shared stressor.